(untitled) (Journal of Technology and Operations Management, 2019)
The global climate system began posing risks for human and natural systems on all continents and across oceans. It is therefore essential to identify and adopt solutions that sustainably increase rice production and strengthen crops’ resilience to climate variabilities. The ecosystem-based crop management technique of the System of Rice Intensification (SRI) is an alternative solution in environmental development plans. In line with the need of developing climate-smart farming management, this narrative review aims to address to SRI adoption as a transition to more productive, inclusive and sustainable agriculture that promotes the use of climate-resilient crops. The review provided evidence that SRI is beneficial to address sustainable agricultural practices and enhance resilience against climate change. In conclusion, SRI-based paddy farming responds to the need for a sound functioning of agriculture management and build climate resilience.